2000
DOI: 10.1161/01.str.31.10.2307
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension as a Risk Factor for Stroke

Abstract: Background and Purpose-The association between orthostatic hypotension (OH) and stroke has rarely been investigated in longitudinal studies. The purpose of the present study was to determine whether OH predicts ischemic stroke in a middle-aged, biethnic population after adjustment for known stroke risk factors. Diastolic, systolic, and consensus OH were evaluated for baseline associations and for the ability to predict stroke. Methods-In 11 707 persons from the Atherosclerosis Risk in Communities (ARIC) cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
119
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(128 citation statements)
references
References 67 publications
(70 reference statements)
6
119
1
2
Order By: Relevance
“…[1][2][3]5,6,10,11,13,14 In the current report, lower BMI was positively related to an excess in the odds of OH. Although findings were adjusted for age, hypertension, diabetes, cigarette smoking, total cholesterol, HDL cholesterol, and triglycerides, other unknown comorbidities in leaner individuals are likely to have contributed to this finding.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…[1][2][3]5,6,10,11,13,14 In the current report, lower BMI was positively related to an excess in the odds of OH. Although findings were adjusted for age, hypertension, diabetes, cigarette smoking, total cholesterol, HDL cholesterol, and triglycerides, other unknown comorbidities in leaner individuals are likely to have contributed to this finding.…”
Section: Discussionsupporting
confidence: 56%
“…In the Atherosclerosis Risk in Communities (ARIC) study, which is a survey of Caucasian and Black men and women aged 45-64 years, prevalence was 5%. 1,2 This difference in the prevalence of OH between studies is largely due to methodological differences. As noted in our methods, we measured supine BP three times after at least 5-min of rest and a single standing BP at 0 and 2 min of standing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, sudden recurrent decreases in BP with standing could contribute to end‐organ damage. Several studies have shown OH to be associated with diseases of end‐organ hypoperfusion, such as stroke40 and peripheral artery disease 13. In our study, the association between OH and detectable hs‐cTnT may indicate microischemia from recurrent hypoperfusion of coronary vessels 29.…”
Section: Discussionmentioning
confidence: 52%